The genome of the versatile nitrogen fixer Azorhizobium caulinodans ORS571 - Lee, Kyung-Bum (BioMed Central, 2008)
BACKGROUND: Biological nitrogen fixation is a prokaryotic process that plays an essential role in the global nitrogen cycle. Azorhizobium caulinodans ORS571 has the dual capacity to fix nitrogen both as free-living organism and in a symbiotic interaction with Sesbania rostrata. The host is a fast-growing, submergence-tolerant tropical legume on which A. caulinodans can efficiently induce nodule formation on the root system and on adventitious rootlets located on the stem. RESULTS: The 5.37-Mb genome consists of a single circular chromosome with an overall average GC of 67% and numerous islands with varying GC contents. Most nodulation functions as well as a putative type-IV secretion system are found in a distinct symbiosis region. The genome contains a plethora of regulatory and transporter genes and many functions possibly involved in contacting a host. It potentially encodes 4717 proteins of which 96.3% have homologs and 3.7% are unique for A. caulinodans. Phylogenetic analyses show that the diazotroph Xanthobacter autotrophicus is the closest relative among the sequenced genomes, but the synteny between both genomes is very poor. CONCLUSION: The genome analysis reveals that A. caulinodans is a diazotroph that acquired the capacity to nodulate most probably through horizontal gene transfer of a complex symbiosis island. The genome contains numerous genes that reflect a strong adaptive and metabolic potential. These combined features and the availability of the annotated genome make A. caulinodans an attractive organism to explore symbiotic biological nitrogen fixation beyond leguminous plants.